Penamaan Sapaan Kekeluargaan Masyarakat Melayu di Pematang Ibul - Haryani Pitri; Aprilia Susanti; Mr. Arfan; Sandra Gita Wardany (UIR Press, 2023)
Each region has the characteristics of different greetingmwords. Greeting words are intended to greet, reprimand, and mention specialmpronouns in communication. This research was conducted in Pematang Ibul Village, which is located in Rokan Hilir Regency. This study aims to determine the naming andmgreeting of the Malay community of Pematang Ibul, Rokan Hilir Regency. Data collection techniques used are listening, note-taking and interviewing techniques. Data were analyzed using qualitative data analysis techniques. The populationmin this study are all the names used by the Malay communitymof Pematang Ibul, Rokan Hilir Regency. The research method used is descriptive method. Based on themtheory that has been put forward, theremare 16 analysis of greetings in themMalay community of Pematang Ibul, Rokan HilirmRegency.